(untitled) (Economics and region, 2019)
International human rights standards are based on the idea of each person participating in public life on the basis of equality and non-discrimination. Ensuring inclusive growth today is the main strategic vector for the development of the national economy of the leading countries. The paper systematizes the priorities of inclusive development of the national economy. The content, components and types of models of inclusive development of the national economy are disclosed. The authors proposed macroeconomic indicators of the achievement of the level of development of the national economy on an innovative, sustainable and inclusive basis.